Quantities and qualities of fecal sludge: Experiences from field implementation with a Volaser in 7 countries during a pandemic - Andriessen, Nienke; Appiah-Effah, Eugene; Browne, Shirley Josephine Iyamide; al Jahjah, Rita; Kabika, Joel; Kinobe, Joel Robert; Korir, Naomi; Nishimwe, Pius; Niwagaba, Charles Buregeya; Pradeep, Rohini; Prasad, Prerna; Tembo, James Madalitso; et al. (Frontiers in Water, 2023)
Reasonable estimates for quantities and qualities (Q&Q) of faecal sludge that accumulate in onsite sanitation containments are fundamental for the design of appropriate management and treatment solutions, from community to city-scale. There are increasing attempts to improve Q&Q estimates, but current approaches are still at a conceptual level, and are not yet standardized with confirmed statistical relationships. To reach this level, we will need consistent approaches for planning, measuring, and global collaborations. Hence, the objectives of this study were: 1) to assess and compare Q&Q of faecal sludge from seven cities and communities, and explore statistical relationships that could be used to increase accuracy of Q&Q estimations; 2) to test and launch the Volaser device for measuring in situ volumes of faecal sludge; and 3) to capture lessons learned from field implementation with collaborators in seven countries during a global pandemic when no international travel was possible. The study took place in Ghana, India, Lebanon, Kenya, Sierra Leone, Uganda, and Zambia during the Covid-19 pandemic. Q&Qs were measured in 204 containments with a Volaser, laboratory analysis, and questionnaire. Results indicate that there are differences in Total Solids (TS) and Chemical Oxygen Demand (COD) in faecal sludge based on containment type, toilet type, source, and whether there is a water connection on the premises. Based on the results of this study, together with previously published open-source data, an empirical relationship for Volatile Solids (VS) and TS of 0.49 (R2=0.88) was established using 1,206 data points. For COD/TS, no significant relationship was observed. Developing such empirical relationships will be useful for planning and modelling approaches. An external evaluation was conducted to evaluate overall project management, Volaser technology transfer, and effects of collaborating during the Covid-19 pandemic. Success factors for collaborating with new and existing partners without face-to-face meetings included laboratory capacity and experience with analytical methods, study objectives that were relevant for the partner and locality, and a strong quality assurance plan to ensure comparability of results. The lessons learned can be taken forward as ways to reduce carbon footprint, and contribute to resilient, inclusive development research projects.